Analysis of Mode Choice Between Damri Bus and Taxi Services as an Effort to Improve Passenger Transportation Services : (Case Study: Gemeh–Melonguane) - Anisya Thalita D. Maratade; Lucia Ingrit Regina Lefrandt; Semuel Yacob Recky Rompis (Lembaga Pengembangan Kinerja Dosen, 2025)
The Gemeh–Melonguane route experiences a high volume of passenger trips, with noticeable competition between Damri buses and taxis as the primary transportation modes. Passengers' mode selection is influenced by various individual considerations and situational factors. This study aims to examine the characteristics and key factors affecting passenger decisions in choosing between Damri buses and taxis on this route. A descriptive quantitative method is applied, combining descriptive analysis to explain user characteristics with multiple linear regression to identify significant influencing factors. The regression results are then processed using a binomial logit model to estimate the probability of mode choice. The utility function derived from the regression analysis is Yubd = -3.027 + 2.417X10 + 3.85X23 + 4.052X24 + 4.659X31 + 4.289X32 + 3.388X33 + 2.352X34 - 3.653X61 - 4.377X62 - 2.629X72 + 1.325X82. Six variables were found to significantly influence mode selection: gender (X1), age (X2), occupation (X3), luggage weight (X6), reason for choosing the mode (X7), and service perception (X8). The coefficients of these variables were input into the binomial logit model to determine the likelihood of choosing each transport mode. The findings reveal that the probability of selecting Damri buses is 82%, while the likelihood of choosing taxis is 18%. These results indicate that Damri buses are more likely to be chosen due to factors such as affordability, convenience, and passenger demographics.